(untitled) (Sambahak: Human Rights Journal, 2025)
The National Human Rights Commission (NHRC) Nepal is a constitutionally established institution dedicated to the protection and promotion of human rights. This article critically examines the comprehensive role of the NHRC Nepal by analyzing its legal mandate, institutional structure, and operational mechanisms. The commission plays a pivotal role in monitoring government actions, investigating human rights violations, raising public awareness, and recommending policy and legal reforms to promote justice, equality, and dignity for all citizens. As a guardian of civil, political, economic, social, and cultural rights, the NHRC Nepal engages in educational outreach, collaborates with civil society, and offers consultative advice to government agencies. These efforts aim to bridge the gap between constitutional guarantees and ground realities. However, despite its achievements, the Commission faces several institutional challenges—including limited financial and human resources, delays in investigation, and the non-binding nature of its recommendations—which undermine its effectiveness. This article underscores the urgent need for structural and operational reforms to enhance the NHRC Nepal’s autonomy, enforcement capacity, and outreach. Furthermore, by aligning its work with international human rights frameworks and participating in global networks such as the Asia Pacific Forum and United Nations Human Rights Council reviews, the NHRC Nepal contributes to the global dialogue on human rights protection. Addressing these gaps will not only improve its domestic performance but also strengthen its legitimacy and impact on the international front.